The effect of Clusterin level as a potential marker in women with polycystic ovary syndrome - Ali Numan, Hiba; G.M. Almohanna, Thualfeqar; Q. Almayali, Mohammed.; Adday Ali, Rawaa; Khazal Abdulghareeb Taha, Hanaa; Addai Ali, Hanaa (Edelweiss Applied Science and Technology, 2024)
An organ with high metabolic activity, adipose tissue secretes a variety of adipocytokines that control the metabolism of fats and carbohydrates and advance insulin resistance (IR). It is currently unclear what pathophysiological mechanism underlies PCOS. In most cases, IR and metabolic abnormalities coexist with PCOS, a chronic endocrine and metabolic illness. Prompt identification and intervention aid in enhancing patients' quality of life while delaying the development of associated issues. Adipokine clusterin (encoded by CLU) is new. Diabetes and obesity-related populations have higher serum clusterin levels. In order to establish a foundation for early PCOS screening, diagnosis, and therapy, the current study examined variations in serum CLU levels in PCOS patients along with their relationships to sex hormones and metabolic markers. A case-control study design consisting of ninety newly diagnosed PCOS patients of ages ranging between (18-42) years have been recruited according to the Rotterdam criteria of PCOS diagnosis. To compare the results, 90 apparently healthy women of age were matched with the patients' group as a control group. Serum clusterin, fasting insulin (FIN), and fertile hormones have been measured in sera using the enzyme-linked immune sorbent assay (ELISA) technique. An independent t-test analysis was performed on the data. Pearson correlation was utilized to evaluate the relationship between the variables. It was found that the PCOS patients had considerably greater serum CLU (41.672± 3.85 vs. 28.5845± 3.01 μg/ml, P < 0.001) than healthy women. A multiple stepwise linear regression analysis showed that HOMA-IR was separately linked with BMI, and HOMA-IR were independently associated with CLU (P < 0.05). Serum CLU exhibited a positive connection (P < 0.05) with BMI, FSG, FINS, and HOMA-IR. Serum CLU in the PCOS group correlated well with TG, CLU, HOMA-IR, FSH, FSG, and FINS. The PCOS women group significantly outperformed the fertile, healthy women group regarding BMI, LH, FSH, FSG, FIN, HOMA-IR, TC, TG, and LDL-C levels. They also had lower levels of HDL-C and QUICKI values. Additionally, serum clustrein levels. 31.68 A cut-off value of CLU as a marker for diagnosing PCOS with a sensitivity of 90.0% and a specificity of 87.5% (AUC: P value = ˂0.0001, 0.887-1.000.